Prospective randomized study to evaluate and compare the post-procedural sexual function in patients undergoing semi-rigid ureterorenoscopy for distal ureteric stones in three different operating room settings - Gajanan S. Bhat; Anuradha Shastry (Asian Journal of Urology)
Objective: To evaluate and compare the effect of semi-rigid ureterorenoscopy on post-procedural sexual function with three different operating room settings. Methods: In this prospective randomized study, consecutive sexually active patients with normal pre-operative sexual function undergoing uncomplicated semi-rigid ureterorenoscopy for distal ureteric stones were randomized into three groups, with three different operating room settings. Procedure-related anxiety and sexual function were assessed pre-operatively using Amsterdam Preoperative Anxiety and Information Scale and Brief Sexual Function Inventory (in males) and Female Sexual Function Index-6 (in females), respectively. All the participants were stented following the procedure, and the stent was removed after 3 weeks. Post-procedural sexual function and general discomfort were assessed and compared between three groups at 1 week, 3 weeks, and 12 weeks. The effect of surgery-related anxiety, preoperative sexual function, age, and general discomfort (including stent-related discomfort) on post-procedural sexual function were analyzed using multiple regression analysis. A p-value of less than 0.05 was considered statistically significant. Results: Totally, 327 eligible patients were randomized into three groups. The group of patients who underwent the procedural with a screen separating the operating area from the patient vision, while the patient could watch the endoscopy through a separate monitor, had better post-procedural sexual function compared to those who had total vision of the operating area as well as to those whose eyes were blocked. This difference was statistically significant. This post-procedural reduction in sexual function could not be attributed to in situ stent alone. Conclusions: Our study showed that semi-rigid ureterorenoscopy can have significant negative effect on sexual function, which can be reduced with proper preoperative counseling and an ideal operating room settings.